Additions to the list of Lepidoptera (Insecta, Lepidoptera) of North Kazakhstan - Svyatoslav A. Knyazev (Acta Biologica Sibirica, 2024)
The article presents the results of studying the fauna of Lepidoptera in the North Kazakhstan region in the field season of 2023. An annotated check-list includes 162 species from the families Psychidae, Plutellidae, Depressariidae, Autostichidae, Gelechiidae, Pterophoridae, Pyralidae, Crambidae, Tortricidae, Cossidae, Sesiidae, Hesperiidae, Papilionidae, Pieridae, Lycaenidae, Nymphalidae, Satyridae, Drepanidae, Geometridae, Lasiocampidae, Lemoniidae, Endromididae, Sphingidae, Notodontidae, Arctiidae, Erebidae, Noctuidae. 47 species reported from the North Kazakhstan region for the first time.